Student Response in Receiving Distance Learning: Case Study at SMAN 1 Baureno - Kusumaningrum, Novia Widianti; Purnomo, Tarzan (Unnes Science Education Journal, 2020)
This study aims to determine the responses of students in receiving distance learning. This type of research is quantitative descriptive. This trial phase of research was conducted at Baureno 1 High School, tested to class X MIA 1, MIA 5, IPS 3 and IPS 4. The type of data obtained is interview and questionnaire data. Interviews were conducted with teachers of Physics, Language, and Sports and questionnaires were given to students. Based result on the analysis and discussion that has been done shows that 76.8% students of MIPA dan 73.6% students of IPS have a positive response to distance learning, but students do not agree on some other situations such as direct contact with the teacher is needed in learning. Supported in the questionnaire statement number 8 which only got a score of 75 for MIPA and 57 for IPS. This value indicates the smallest score compared to the values ​​of other statements. Therefore, it can be concluded that to support distance learning more effectively requires the ability of teachers to use ICT so that innovative and interactive learning can be created, and this can be proven by the results of interviews. In addition, learning methods and teacher skills are needed to increase students' understanding of the material being studied.